Systematic Literature Review: Utilization of Agricultural Waste as Raw Material for Renewable Energy Biobriquettes - Ilahiyah, Fitratul; Ruyani, Aceng; Firdaus, Muhammad Lutfi (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2026)
The global energy crisis and environmental degradation caused by fossil fuel consumption have driven the search for sustainable alternative energy sources. Agricultural waste, which is abundant and often underutilized, has significant potential as raw material for biobriquettes in renewable energy production. This Systematic Literature Review (SLR) aims to comprehensively analyze research related to the utilization of agricultural waste as biobriquette feedstock during the period 2012-2025. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method was used to screen 200 articles from Web of Science, Scopus, and Google Scholar databases, with 40 articles meeting the inclusion criteria. The review results show that agricultural wastes such as rice husks, corn cobs, bagasse, and coconut shells have competitive calorific values (3.000-7.000 cal/g) meeting solid fuel standards. Factors affecting biobriquette quality include raw material type, binder type (tapioca, molasses, clay), compaction pressure (100-1,000 kg/cm²), and particle size. Indonesia, with agricultural waste production reaching 136 million tons per year, has biomass energy potential of 49.810 MW. Biobriquette development not only offers effective waste management solutions but also contributes to greenhouse gas emission reductions of up to 335.679 tons CO₂-eq per 100,000 tons of biobriquettes. This SLR identifies research gaps and provides recommendations for developing more efficient and sustainable biobriquette technology.